Investigation into the Chaoticity Systems of Galaxy Triplets Based on the N-Body Numerical Simulation - Wu, Yinqi (Transactions on Computer Science and Intelligent Systems Research, 2025)
With more attention being put on the dynamic evolution of celestial bodies, the system of galaxy triplets has been considered as an important and helpful dynamic system to understand the gravitational interaction between stars and clusters in the universe. However, the analysis of the chaoticity of the system of galaxy triplets was still not emphasized as much as the system of three point masses. By setting the same initial conditions of L4 on the system of extended masses and the system of point masses, and using chaos indicators, including Mean Exponential Growth of Nearby Orbits and Maximum Lyapunov Exponent, the chaoticity of each system is quantified and compared. The paper found that many orbits of extended masses are likely to be more stable than orbits of point masses. A possible explanation for this result is that the dynamic friction between extended masses dissipates the system’s energy, contributing to fewer unbounded orbits. Hence, more orbits are likely to be stable and bounded.